Collaborative Online International Learning (COIL): University students’ feedback to international communication in Japan - Adam L. Miller; Rajib Ali (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
Collaborative Online International Learning (COIL), has been an accessible tool for online collaboration and learning for close to 20 years. Previous papers have explored the potential benefits of this teaching approach in regards to improved language acquisition, increased cultural awareness, and the potential to enrich learning environments. The aim of this paper is to acquire feedback from university students in Japan who have completed a COIL program, to see how they perceive the experience; in so doing, it is hoped that this study can inform how Japanese university students perceive their participation in a COIL program, with a focus on its impact on intercultural communication, language development, and collaborative learning. A mixed-methods approach was employed, including a Likert-scale questionnaire and open-ended responses from 21 first-year students at a private university in Nagoya City, Japan, after completing a 7-week COIL program with a North American university.While small in scale, the study found that although some logistical and technical difficulties were raised by the students, their experience with COIL was an enjoyable and rewarding one. The study contributes to the existing literature by offering student-centered insights into COIL experiences in Japan and proposes a practical implementation model (GORMS) for future programs.